OPPORTUNITIES OF THE EDUCATIONAL PROCESS BASED ON DIFFERENTIAL APPROACHES - Babayeva Maxfuza Abduvaitovna (Bright Mind Publishing, 2025)
The article presents theoretical foundations, practical ways and methodical recommendations for implementing differential approach in education. The differential approach allows you to effectively organize the educational process, taking into account the individual capabilities, level of knowledge and interests of each student. With this approach, learners can demonstrate their full potential and achieve good results.
Keywords: Differential, differential education, differential approach, group work, training, method.